Pkami Accounting and Marketing Training Through Android-Based Applications for MSME Groups Tanggulangin Sidoarjo Golf Bags: Pkami Pelatihan Akuntansi Dan Pemasaran Melalui Aplikasi Berbasis Android Bagi Kelompok UMKM Tas Golf Tanggulangin Sidoarjo - Rahayu, Duwi; Setiawan, Hamzah; Pebrianggara, Alshaf (Universitas Muhammadiyah Sidoarjo, 2022)
Many of the MSME actors still have minimal literacy related to accounting and marketing records, so they focus more on production activities. So that accounting and marketing records become inadequate and can cause the MSMEs to not be able to develop. This can be seen from the existence of the MSME group which sometimes has difficulty knowing whether their business is making a profit or not per month, so that every decision made is not in accordance with the financial condition of MSMEs. Furthermore, the MSME group sometimes feels reluctant to do Android-based marketing. so that it is difficult for their business to develop. This is the key to the problem for the Tanggulangin Golf Bag UMKM group. The Android-based application is one of the choices of the best solution for the Tanggulangin MSME Bag Golf to increase the effectiveness of financial and marketing performance because it can be accessed directly via a smartphone. MSME Accounting Applications and Tokopedia can provide solutions in terms of accounting records and marketing. Based on this, training in accounting and marketing records will be carried out for the managers of the MSME group at Tanggulangin Sidoarjo Golf Bags. The implementation of this training is expected to have a positive impact in increasing understanding of accounting and marketing based on Android and can provide benefits in the economic field for the MSME group, Tanggulangin Sidoarjo Golf Bags.